Implementasi Manajemen Kewirausahaan Program Pendidikan Paket C untuk Peningkatan Mutu Lulusan - Deti Rostini; Wiwik Dyah Aryani; Euis Sumiati; Neneng Nurul Khaerani; Dewinda Bunga Widdian (Journal on Education, 2023)
With a collaborative approach, innovative entrepreneurial development planning can be carried out, the approach in this research uses a qualitative approach and the research method used is an analytical descriptive method. The data collection techniques in this study were through interviews, documentation and observations carried out in order to find out the planning, implementation, assessment, and results of entrepreneurship learning in the C package education program at PKBM An-nur Ibun, Bandung Regency. In the planning stage, the determination of learning objectives that are in accordance with the objectives is carried out, the implementation of learning using a group strategy, assessment is carried out to prove that students have entrepreneurial abilities with criteria of at least 90% of citizens learning to complete participating in entrepreneurship learning programs, and at least 70% of graduates are able to entrepreneurship / strive to be independent. The learning results show that more residents learn to pursue Package C who have a behavioral attitude, knowledge as entrepreneurs. PKBM An-nur Ibun Bandung Regency is expected to continue to be a reference and pilot for the improvement of community learning activity centers (PKBM) in various aspects, especially in providing non-formal educational facilities for residents, by optimizing learning facilities such as the procurement of study groups, skills education, job training, women's empowerment, and the provision of facilities for residents who do not receive formal education or drop out of school.